Reevaluating Pediatric Osteomyelitis with Osteoarticular Tuberculosis: Addressing Diagnostic Delays and Improving Treatment Outcomes - Alexandru Herdea; Harun Marie; Ioana-Alexandra Negrila; Aliss Delia Abdel Hamid Ahmed; Alexandru Ulici (Children)
Background: Pediatric osteoarticular tuberculosis (TB) remains a significant global health challenge, particularly in resource-limited settings, where delayed diagnosis and treatment frequently lead to severe long-term complications. Despite advancements in TB control, skeletal TB in children is often misdiagnosed due to its non-specific clinical presentation, contributing to poor outcomes such as joint deformities, growth disturbances, and chronic pain. The complexity of diagnosing osteoarticular TB is further exacerbated by the limited sensitivity of conventional diagnostic tools and the overlap with other musculoskeletal conditions. This study seeks to evaluate the impact of early detection and multidisciplinary management on treatment outcomes in pediatric patients with osteoarticular TB. Methods: A retrospective review was conducted at the Pediatric Orthopedics Department of the “Grigore Alexandrescu” Children’s Hospital in Romania from 2009 to 2023. Case data included clinical, imaging, and microbiological findings, and treatment outcomes in children aged 0–18 years diagnosed with tuberculous osteomyelitis. Results: The study identified varied clinical presentations, with delayed diagnosis often linked to misinterpretation of symptoms as non-TB infections. Multimodal diagnostic approaches combining imaging, microbiological testing, and histopathology improved diagnostic accuracy. Early surgical intervention alongside anti-TB therapy proved effective in reducing long-term complications. Conclusions: Timely, accurate diagnosis and multidisciplinary treatment are critical to improving outcomes in pediatric osteoarticular TB. Vaccination status and comprehensive diagnostic tools significantly influence disease progression and treatment success. The study underscores the need for enhanced screening and diagnostic methods to prevent delays in treatment.